STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA PENDIDIK MELALUI MANAJEMEN SUPERVISI - Riskiyah, Eka Maftuhatil (MPI STAI Sangatta Kutai Timur, 2024)
Educating the nation's life and creating quality human resources can be pursued through education. To create this, of course, professional educators are needed so that the education process runs well. Therefore, it is necessary to improve the performance of a teacher. Therefore, this study aims to inform about the strategies carried out by school principals in improving the performance of educators/teachers in their institutions. This study uses qualitative methods with the type of literature study research. The results of this study explain that the principal uses supervision management from planning, implementation, supervision, and even evaluation as a strategy for improving the performance of a teacher. Supervision carried out by the principal is very important in improving teacher performance because supervision can facilitate teachers in improving their competence. Of course, with several strategies including coaching, supervision, motivating, and evaluating teacher performance.